Mikroračunalniške arhitekture: Zbirka rešenih nalog - Brezočnik, Zmago (University of Maribor Press, 2025)
Microcomputer Architectures: Collection of Solved Problems. This collection of solved problems is primarily intended as a study aid for students preparing for midterm tests and written exams involving calculation-based tasks in the field of microcomputer structures, microprocessors, and microcontrollers. The problems are organized into chapters that cover computer performance, communication between main computer components, cache memory, internal and external memory, input-output organization of microprocessors, instruction sets of the central processing unit, addressing modes and instruction formats, and assembly language programming. The final chapter focuses on testing knowledge through the analysis of code segments and the writing of short programs for Intel x86 and ARM microprocessors.